Developmental dynamics of neurotensin binding sites in the human hypothalamus during the first postnatal year - Najimi, Mohamed; Sarrieau, Alain; Kopp, Nicolas; Chigr, Fatiha (Frontiers in Cellular Neuroscience, 2014)
The aim of the present study was to determine a detailed mapping of neurotensin (NT) in the human hypothalamus during the first postnatal year using an in vitro quantitative autoradiography technique and the selective radioligand monoiodo-Tyr3-neurotensin (2000 Ci/mM). Ten human postmortem hypothalami (aged from 2 hours to 1 year of postnatal age) were used. The binding constants were of high affinity (nanomolar range) and similar between all cases investigated. Furthermore, competition experiments showed insensitivity of these receptors to levobacastine. Autoradiographic distribution showed that NT binding sites were widely distributed throughout the rostrocaudal extent of the hypothalamus. This distribution was not homogeneous and regional variations existed. The highest densities were present mainly in the anterior hypothalamic level, especially in the preoptic region . Important NT binding site densities were also present at the mediobasal level, particularly in the paraventricular, parafornical and dorsomedial nuclei. At the posterior level, low to very low densities were observed in all the mammillary complex subdivisions, as well as in the posterior area. Although this topographical distribution was almost identical in each age period analyzed, age-related variations existed; the densities were higher in preoptic area of neonates compared to older infants.The developmental profile was characterized by a progressive decrease in NT receptors from the neonate period to 1 year of postnatal age with a tendency to reach adult levels. On the other hand, the low levels of NT binding sites observed in posterior hypothalamus did not vary during the first postnatal year. In conclusion, the present study demonstrates the occurrence of important NT binding sites density in different many regions of the human neonate/infant hypothalamus that are involved in the control of neuroendocrine and/or neurovegetative functions.